Resilience and Self-Leadership as Moderators of Academic Stress and Burnout Among Thai University Students - Smithikrai, Chuchai; Smithikrai, Bhudis (The Journal of Behavioral Science, 2024)
The objectives of this study were twofold: (1) to investigate the relationship between academic stress and academic burnout among Thai university students; and (2) to examine the moderating roles of resilience and self-leadership in the relationship between academic stress and academic burnout among Thai university students. Employing an anonymous questionnaire survey, the study involved a sample of 601 undergraduate students enrolled in Thai universities. The research instruments comprised four questionnaires: (1) an academic stress scale, (2) an academic burnout scale, (3) a resilience scale, and (4) a self-leadership scale. The hypotheses regarding moderating effects were evaluated using the SPSS Program with the PROCESS macro (Model 2). The results unveiled a significant positive link between academic stress and academic burnout (b = 1.12, SE = .19, p < .01). Additionally, the results indicated that higher levels of resilience (b = -.09, SE = .04, p = .03) and self-leadership (b = -.09, SE = .05, p = .05) had a dampening effect on how academic stress influenced students' experiences of academic burnout. This study provides substantial implications for educational institutions. It underscores the importance of implementing resilience training programs, incorporating self-leadership principles into educational frameworks, and launching mentorship initiatives aimed at nurturing these essential attributes among students. By understanding and harnessing the moderating potential of resilience and self-leadership, universities can actively contribute to the well-being and academic achievements of their students, ultimately fostering a more supportive and empowering educational environment.